1998
DOI: 10.1046/j.1365-2648.1998.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment of dying patients: the strategies and barriers to patient autonomy

Abstract: The growing debate about the ability of the nurse to empower patients has featured frequently in the nursing journals over recent years. This paper seeks to address the issue around the need to empower dying patients by an examination of nurses' written reflections on critical incidents in their practice. Geertz's 'thick description' has been used to interpret the data. The issues of power and professionalism are central to the discussion. The results are tentative given the sample size but point towards a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…This is endorsed by the literature on patient empowerment (Hewison 1995, Martin 1998) and participation in decisions (Ashworth et al 1992, Jewell 1994. This is endorsed by the literature on patient empowerment (Hewison 1995, Martin 1998) and participation in decisions (Ashworth et al 1992, Jewell 1994.…”
Section: Implications Of the Findingsmentioning
confidence: 85%
“…This is endorsed by the literature on patient empowerment (Hewison 1995, Martin 1998) and participation in decisions (Ashworth et al 1992, Jewell 1994. This is endorsed by the literature on patient empowerment (Hewison 1995, Martin 1998) and participation in decisions (Ashworth et al 1992, Jewell 1994.…”
Section: Implications Of the Findingsmentioning
confidence: 85%
“…Self‐determination is seen as a patient's resource that could be supported by strengthening the preconditions for self‐determination and by using different nursing interventions. This implies a transfer of power or authority from healthcare professionals to the patient, increasing opportunities for choice 43 and the freedom to make choices 44 . Further ways to promote self‐determination are: a new kind of nursing and management culture, the development of models and methods supportive of self‐determination, and noticing and respecting self‐determination in nursing practice.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Studies that were found which examined this social context of unequal power were related to patient decision‐making (Taylor et al. , 1989) patient autonomy (Martin, 1998), and mental health service needs of psychiatric mental health patients (Jackson & Stevenson, 2000). Hewiston (1995) and Johnson and Webb (1995) studied power dimensions in nurse–patient interactions.…”
Section: Nurse Communication Within Nurse–patient Interactionmentioning
confidence: 99%